2012
DOI: 10.1590/s1726-46342012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de suplementos con multimicronutrientes Chispitas® y anemia en niños de 6 a 35 meses: estudio transversal en el contexto de una intervención poblacional en Apurímac, Perú

Abstract: RESUMENObjetivos. Evaluar la implementación del programa de suplementación universal con multimicronutrientes "Chispitas ® " en la región Apurímac a través de la cantidad y calidad de sobres consumidos y su relación con la anemia, en niños de 6 a 35 meses. Materiales y métodos. Se realizó un estudio transversal usando un muestreo multietápico en el 2010. Se consideró como anemia a los valores de hemoglobina ajustados por altitud menores de 110 g/L. El consumo de multimicronutrientes se categorizó en: menor de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1
22

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 28 publications
1
16
1
22
Order By: Relevance
“…MNPs are distributed during well-child check-ups and promoted through free home visits and informational sessions in public health establishments (Ministerio de Salud, 2014). However, an early study of the nationwide programme showed low adherence to MNP, with only 24.4% of children consuming more Research findings on MNP use in Peru suggest that misconceptions around preparation of MNP, nausea or dislike of taste upon consumption, and negative comments from family and peers were key barriers to adherence (Creed-Kanashiro et al, 2016;Huamán-Espino et al, 2012;Munares-García & Gómez-Guizado, 2016). This research identifies the key facilitators as familial support, culturally appropriate counselling techniques, and recognition of improved child health (Creed-Kanashiro et al, 2016;Huamán-Espino et al, 2012;Munares-García & Gómez-Guizado, 2016).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…MNPs are distributed during well-child check-ups and promoted through free home visits and informational sessions in public health establishments (Ministerio de Salud, 2014). However, an early study of the nationwide programme showed low adherence to MNP, with only 24.4% of children consuming more Research findings on MNP use in Peru suggest that misconceptions around preparation of MNP, nausea or dislike of taste upon consumption, and negative comments from family and peers were key barriers to adherence (Creed-Kanashiro et al, 2016;Huamán-Espino et al, 2012;Munares-García & Gómez-Guizado, 2016). This research identifies the key facilitators as familial support, culturally appropriate counselling techniques, and recognition of improved child health (Creed-Kanashiro et al, 2016;Huamán-Espino et al, 2012;Munares-García & Gómez-Guizado, 2016).…”
mentioning
confidence: 88%
“…Moreover, anaemia is higher in the jungle and highland regions (53.6 and 52.0%) compared with coastal areas (39.3%; Instituto Nacional de Estadística e Informática, 2018). In response to the high rates of anaemia, the Peruvian Ministry of Health implemented a pilot programme in 2009 distributing free MNP to children aged 6-36 months in three Andean regions (Huancavelica, Ayacucho, and Apurímac;Huamán-Espino et al, 2012) and in 2010, expanded to Cajamarca (Creed-Kanashiro, Bartolini, Abad, & Arevalo, 2016). The programme was then implemented nationwide in 2014 (Ministerio de Salud, 2014; Munares-García & Gómez-Guizado, them daily for 12 months, a departure from pilot tests, which recommended consumption every other day for 6 months (Creed-Kanashiro et al, 2016;Ministerio de Salud, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Realizamos un análisis secundario de la base de datos de la Evaluación de la suplementación con MNP en niños de 6 a 35 meses de edad de Apurímac, ejecutada por el Centro Nacional de Alimentación y Nutrición (CENAN) (9) . El diseño del estudio original comprendía dos evaluaciones transversales; la evaluación basal en 2009 (sin distribución de MNP) y la final en 2010 (con distribución de MNP), para el estudio usamos la información de las dos evaluaciones.…”
Section: Diseño De Estudiounclassified
“…Se eligió este suplemento porque la evidencia mostraba mayor aceptabilidad frente al sulfato ferroso (7,8) . A la fecha, se han publicado dos estudios sobre la efectividad de esta intervención piloto, con resultados diferentes, el primer estudio no encontró efectividad de los MNP para reducir la anemia al comparar las prevalencias regionales en Apurímac para los 2009 y 2010 (9) . Mientras que, el segundo estudio, con un diseño de vigilancia centinela en 29 establecimientos de salud del Ministerio de Salud (MINSA) de las tres regiones, reportó una reducción de 37 puntos porcentuales en la prevalencia de la anemia (10) ; sin embargo, la estimación del impacto podría tener algunos sesgos, debido a la pérdida de la muestra (11) (42% del total) y por no contar con grupo control (12) .…”
Section: Mensajes Clave Introducciónunclassified